Ergonomic Assessment of a Manual Fodder Cutter - Kumar, Adarsh; Singh, J K; Singh, Charanjit (Journal of Agricultural Engineering, 2010)
Experiments were conducted to determine the human energy expenditure in operating a manual chaff cutter. Three operators of different age groups were selected for the study. Three different types of fodder crops viz. maize, pearl millet and sorghum were selected for the experiments. Calibration was done for all the three operators on bicycle ergometer and calibration equations were determined. There was increase in energy expenditure with increase in feeding rate. Energy consumption was much higher than the sustainable level of 35% VO2 max for all the dry and green fodder. Specific energy increased with increase in diameter of stalk. Specific energy also varied with material, and was lower in case of dried material of similar diameter. There was mismatch between the energy expenditure by an operator and the energy requirement for cutting of the crops for sustainable operation.